Race Against Diabetes: development and validation of a serious game prototype for school-based health education - Natalia S. Costa; Karanini P. Oliveira; Mateus C. Avelar (Revista Latinoamericana de Tecnología Educativa)
The global rise in the incidence of diabetes mellitus, particularly among children and adolescents, highlights the need for innovative educational strategies in school settings. Serious games have proven promising for improving self-care and preventing complications by combining playfulness with evidence-based content. This methodological study was conducted in two phases: the development of the digital prototype Race Against Diabetes and its validation with experts (n = 6) and the target population (n = 20, aged 11–14). The content adhered to the ADCES7 guidelines and those of the Brazilian Diabetes Society and was assessed using the CVC, I-CVI, S‑CVI/AVE, binomial test, and a Likert-based usability scale. The game is a 2D title developed in Unity/C++, featuring five levels focused on collecting healthy foods and learning about self-care. It achieved an S-CVI/AVE of 0.87, with some items showing a minimum I-CVI of 0.66 (p > 0.05). Usability was rated as satisfactory (mean score: 9.3 ± 2.65), with participants highlighting motivation, clarity, and learning. Race Against Diabetes shows strong potential as a pedagogical tool in health education, promoting knowledge and self-care skills through interactive gameplay. The pixel art design, chosen by students, further enhances engagement. Expansion to other platforms and long-term clinical impact studies are recommended.